Trend: World Bank (2024-02-01). Gender Statistics: General Economic Conditions | Australia, Austria, Belgium, Canada, Chile, Czech Republic, Denmark, Estonia, Finland, France, Germany, Greece, Hungary, Iceland, Ireland, Israel, Italy, Japan, Latvia, Lithuania, Luxembourg, Mexico, Netherlands, New Zealand, Norway, Poland, Portugal, Slovakia, Slovenia, South Korea, Spain, Sweden, Switzerland, Turkey, United Kingdom, United States | GDP growth (annual %) | GDP per capita (current US$), 1980 - 2020. Sage Data. ... - World Bank (Sage Data. Sage Publishing Ltd, 2024)
Indicators provide general data on economic development levels, including gross domestic product, gross national income, poverty headcounts, and more, in developing and advanced economies, as available. ...